Theatre in Algeria and children: a dialogue on history, culture, and ambiances - Makhloufi, Lilia; Fitzsimmons Frey, Heather (My University, 2016)
The dialogue that follows deals with theatre and children in Algeria, and emphasizes the particular context of its emergence and development. It arises from an academic research project concerning ambiances in Algeria, initiated and directed by Lilia Makhloufi. Because of their artistic, cultural and imaginary dimensions, and their effects on Algerian society and young people in particular, theatre spaces were a case study in this research.1 As readers of the dialogue will see, theatre in Algeria has evolved in response to different theories and practices, some related to political or spiritual ideologies, others based on cultural or artistic concerns. Some theatre processes focus on a story, some on an event, and others act as catalysts for social change. When the editors invited us to connect for this dialogue, we were enthusiastic. Heather knew nothing about performance practices or childhood in Algeria and was keen to have an opportunity to learn more. Meanwhile, Lilia was working in a non-dominant language, answering questions about Algerian context, and trying to satisfy Heather’s curiosity about culture, politics, aesthetics, and intentions in creating theatre for and with children. The process proved to be challenging because we carried out the conversation via email whilst in different time zones and countries. By the end, both of us found that the whole process opened our minds to other ways of thinking about the significance of theatre practices, and ways a culture of theatre for young people might develop and be fostered. We hope that the publication of this dialogue will have similar impact for the readership of RIDE.
Keywords: theatre practices; children; Algeria